School and Local Development: meeting and clash - Naira Lisboa Franzoi; Damiana Matos Costa França; Maria Clarice Rodrigues de Oliveira (Universidade Federal de Santa Catarina, 2017)
It presents reflections from two case studies with student workers: the first with workers in a sugar cane plantation, in the northeast of Brazil, and one with tobaco growers, in the south. Both concern to the relationship between workers education, knowledge at work and local development. The data were produced from self-pictures, in the first study, and self- biography, in the second. Among the theoretical references, we take up Schwartz's and Charlot's thesis about knowledge production, and Francisco de Oliveira's and Milton Santos' on local development. The findings can reiterate that the school can only be of effect, when takes into account the cultural heritage of these students.